Glanzmann’s Thrombasthenia Diagnosed following Knee Arthroscopy - John E. Zvijac; Sharhabil S. Ammus; Fernando Aran; Gary M. Kiebzak (Case Reports in Orthopedics)
A 41-year-old man with an unremarkable medical history presented with a painful knee after a sports injury. He was diagnosed with a medial meniscal tear. Symptoms did not abate after 6 months of physical therapy, and he underwent arthroscopic partial medial meniscectomy. A week after beginning physical therapy he experienced a knee effusion, decreased ROM, and inability to flex his quadriceps. His knee was aspirated. Blood tests were ordered and his complete blood count, liver functions tests, and INR/PTT were normal. The patient had recurrent effusions requiring three additional joint aspirations. Ten weeks after the initial surgery, the patient underwent a second arthroscopy, during which a hematoma was removed and a synovectomy performed. The patient continued bleeding from the incisions after portals were sutured, and he was admitted to the hospital. A hematologist was consulted and comprehensive platelet aggregation testing revealed previously undiagnosed Glanzmann’s thrombasthenia. The patient began treatment with platelet infusions and desmopressin and progressed to a full recovery. Clinical suspicion for surgical patients with unusual repetitive postoperative bleeding should include previously undetected rare bleeding disorders even in adults.